Multi-time scale source and load intelligent scheduling method for distribution network based on multi-agent game - Tang Junci; Li Tie; Pi Junbo; Wang Mingkai (Dianzi Jishu Yingyong)
Considering that the user demand will affect the effect of multi-time scale source load intelligent dispatching in distribution network to a certain extent, a multi-agent game based multi-time scale source load intelligent dispatching method is proposed. Due to the fluctuation of power load in the operation process of distribution network, this paper analyzes the multi time scale source load variation scenarios of distribution network, alleviates the pressure of distribution network operation through short-term interaction, and analyzes the source load characteristics of distribution network. Based on multi-agent game, an intelligent optimization objective function of distribution network is built based on multi-agent game. Based on the daily dispatching model of distribution network, the daily 2 h scheduling model of distribution network and the daily 15 min scheduling model of distribution network, a multi time scale source load scheduling model of distribution network is constructed, and the scheduling of multi time scale source load of distribution network is realized. Experimental results show that the proposed method has better scheduling effect in different strategies and scenarios, and is suitable for wide application.